Managing Generation Gap Difference for Working in Digital Age - Kalyanamitra, Ratthiporn; Lakkhanapichonchat, Tassanee; Kalyanamitra, Kamolporn; Biadnok, Chucheep (Asia Pacific Journal of Religions and Cultures, 2024)
The objectives of this research were to assess the problems and obstacles in managing generation gap differences for working in the digital age, to analyze the managing generation gap difference for working in the digital age, and to propose suggestions for managing generation gap differences for working in the digital age. This research was qualitative. Key informants in this study were executives of government organizations, executives of state enterprises, personnel working in government organizations, and personnel working at state enterprise organizations, totaling 20 key informants by a purposive selection. The research instrument was a structured interview. Data were analyzed by a descriptive summary.